A global bibliometric analysis of intimate partner violence in the field of HIV/AIDS: implications for interventions and research development - Tham Thi Nguyen; Tham Thi Nguyen; Lilian Ha; Long Hoang Nguyen; Linh Gia Vu; Linh Gia Vu; Hoa Thi Do; Laurent Boyer; Guillaume Fond; Pascal Auquier; Carl A. Latkin; Cyrus S. H. Ho; et al. (Frontiers Media S.A., 2023)
This study aimed to explore the research landscape of intimate partner violence (IPV)-harm-induced behavior in an intimate relationship and HIV/AIDS to determine lessons learnt and gaps that may be filled by future research. Publications related to IPV, and HIV/AIDS published from 1997 to 2019 were collected from Web of Science (WoS). STATA and VOSviewer software tools were used for bibliometric analysis. Content analysis, common topics, and the map of co-occurrence terms were structured by Latent Dirichlet allocation and VOSviewer software tool. 941 studies were included. Factors associated with domestic violence and interventions to reduce IPV were the two most common themes. Meanwhile, mental health illness among pregnant women affected by HIV and IPV, and HIV-risk among youth suffering from IPV have not received adequate attention. We suggest that more research focusing on adolescents and pregnant women affected by HIV and IPV. In addition, the development of collaborative networks between developed and developing countries should also be addressed.